Thank You to Our 2018 Peer Reviewers. Issue 4 (18th April 2019) - Filippelli, Gabriel; Colwell, Rita; Anenberg, Susan C.; Balbus, John M.; Ceccarelli, Daniela; Hudson‐Edwards, Karen; Jutla, Antarpreet; Miao, Chiyuan; Sandifer, Paul A.; Vengosh, Avner
Abstract: Public trust in science, effective science communication, and rapid and constructive response to authors about their submissions are of paramount importance to the scientific enterprise and indeed to society itself. This is really at the heart of peer review—providing thoughtful insights into both the scientific quality and importance of work, and also how it is communicated to other scientists and increasingly to a broader audience. Very few opportunities exist to acknowledge the mostly anonymous process of peer review, especially given the huge increase in review requests and the relatively mechanical nature of online reviewing platforms. We continue to be humbled by the time, effort, and careful insights that our colleagues share with each other through the process of peer review. In 2018, GeoHealth benefited from more than 83 reviews provided by 53 of our peers for papers submitted to the journal. Thank you all for your awesome efforts toward advancing geohealth now and for the future. Key Point: In 2018, GeoHealth benefited from more than 83 reviews provided by 53 of our peers for papers submitted to the journal